An Integrated Approach to Building Planning Using the Multi-Criteria Decision Method (MCDM) and BIM - Yarramsetty, Subbarao; Faheem, Mohammed; MVN, Siva Kumar (International Journal of Sustainable Construction Engineering and Technology, 2023)
The purpose of this study is to create a method based on an integrated multi-criteria decision-making—building information modelling (MCDM—BIM) approach, which will then be applied to two case studies at various stages of construction. For each case study, three options were developed based on the client's specifications. Dynamo was used as a Revit computational design tool. Based on the "principles of building planning," four important criteria were chosen. A questionnaire was developed for the subjective evaluation of possibilities based on the criteria that were chosen. Later, the ideal floor plan configuration was determined. The use of a combined MCDM-BIM technique enabled the ranking of each design option as well as 3D visualisation of all current and potential design options.